Treatment dropout: the hidden truth behind the treatment failure of malignancy - Chakraborty, Bhaskar; Dhar, Anasuya (International Journal of Research in Medical Sciences, 2022)
Background: Bangladesh is a country with a high burden of malignant people. As this burning issue is recklessly increasing day by day, the aim of this study is to point out the causes behind the cancer patients getting dropped out of the midway of their treatment. Methods: A total of 40 patients were enrolled in this study at a tertiary level cancer hospital. They were selected from the treatment drop out of the registry of our oncology ward, connected through their contact numbers, and several questions were asked systematically according to a pre-formed questionnaire containing patients’ age, gender, socio-economic and educational status, different possible causes of treatment drop out, etc. Data were collected and analyzed systematically with the help of SPSS 25. Results: Among the study population (n=40), the number of male and female patients was 12 (30%) and 28 (70%) respectively. The mean age of male patients was 65 years (range 45 to 78 years) and that of female were 45 years (35 to 60 years. Most of the patients were from lower-middle-class socio-economic status (45%) with an average of educational status up to secondary school certificate (SSC) exam and family income less than 20,000 BDT per month. Only 15% of patients were self-dependent and the rest of all were dependent on either husband (in the case of female) or children. Among twelve male patients (n=12), five patients (5, 41.6%) had colorectal cancer, three patients (3, 25%) had lung cancer and two patients (2, 16.7%) was harboring prostate cancer. Of twenty-eight female study populations (n=28), more than half of the population (15, 53.6%) had breast cancer, one-fourth of patients (7,25%) had cervical cancer and only two patients (2, 7.14%) had ovarian cancer. The possible vital reason behind early treatment dropout among patients was financial problems (55%). Husbands’ deprivation (13%), Social harassment and isolation (8%) after the first cancer diagnosis, Conclusions: Social awareness, proper steps, and policies of government and non-government organizations for cancer patients taking into consideration all of the causative factors behind treatment drop out can reach the goal of cancer-free Bangladesh.